The Future of the Iran Nuclear Deal: Pretty Bright from Its Verification Lens - Mutti Anggitta (International Journal of Nuclear Security, 2017)
This manuscript discusses the JCPOA’s verification mechanism, especially its four innovative additional safeguards measures: much broader monitoring of Iran’s nuclear program, access with a deadline and dispute resolution mechanism, the Procurement Channel, and the prohibition of weaponization activities. It considers the possible implications of such safeguards measures for the future of the deal and for the non-proliferation regime. This manuscript found that the four additional safeguards measures, if implemented with the Iran’s Comprehensive Safeguards Agreement and the Additional Protocol, would increase the effectiveness of monitoring and verification measures under the deal. In short, they will significantly contribute to the success of the deal. The deal is a success if its verification mechanism prevents Iran from producing weapons-grade uranium and weapons-grade plutonium at its declared nuclear facilities for 10-15 years, and deters the country from building clandestine facilities to secretly produce those fissile materials.
Keywords: Iran Deal; JCPOA; Nuclear Safeguards